Study of land suitability for rubber and cashew in the derived savanna zone of Edo State, Nigeria - Lucky Agbogun; Aigboghosa Samson Umweni; Henry Kadiri; Faith Ehinomhen Okunsebor (Jurnal Ilmu Pertanian, 2021)
This study attempted to assess the soil suitability in the derived savanna zone of Edo State, Nigeria for the cultivation of some tree crops. The research specifically aimed to evaluate soil suitability for cashew and rubber supported by suitability maps for both crops. In terms of land suitability evaluation, mapping units 1 and 2, with an area coverage of 27.4 ha of the entire research area (100 ha) were found to be marginally suitable (S3) for rubber cultivation but moderately suitable (S2) for cashew. Mapping unit 3, with area coverage of 38 ha was found to be currently not suitable (N1) for rubber but marginally suitable (S3) for cashew cultivation. Mapping unit 4 representing area coverage of 34.7 ha was found to be permanently not suitable (N2) for rubber cultivation but marginally suitable (S3) for cashew. Thus, technically, rubber can only be cultivated in that land at marginal level with an expected productivity of 27.4 ha (27.4 %). Cashew can be cultivated at moderate and marginal levels with an expected yield of 27.4 ha (27.4 %) and 72.6 ha (72.6 %), respectively, of the total land area. Thus, the preferred crop for the studied is cashew. It is recommended that for any significant investment in cultivation of this crop, the priority is the moderate levels with an expected productivity of 27.4 ha or 27.4 % of total land area.